2015
DOI: 10.1007/s40265-015-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Furoate/Vilanterol: a Review of Its Use in Patients with Asthma

Abstract: Fluticasone furoate/vilanterol (Relvar(®)) is a once-daily, fixed combination of an inhaled corticosteroid (ICS) and a long-acting β2-adrenoreceptor agonist (LABA), delivered via a dry powder inhaler (Ellipta(®)). It is approved for the treatment of asthma in the EU and Japan, and is the first once-daily ICS/LABA to be available for this indication. Fluticasone furoate is an enhanced-affinity glucocorticoid receptor agonist, with potent anti-inflammatory activity. Vilanterol produces rapid and prolonged bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…An indirect bronchial challenge using adenosine 5ʹ-monophosphate (AMP) was performed at various time points after dosage. Single-dose FF and FP showed significant improvements in the provocative concentration of AMP producing a 20% decline (PC 20 AMP) in the forced expiratory volume in one second (FEV 1 [28]. This was the first study to show that FF clinically has a long duration of action, suggesting that it may be compatible with OD dosing.…”
Section: Phase I and Ii Efficacy Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…An indirect bronchial challenge using adenosine 5ʹ-monophosphate (AMP) was performed at various time points after dosage. Single-dose FF and FP showed significant improvements in the provocative concentration of AMP producing a 20% decline (PC 20 AMP) in the forced expiratory volume in one second (FEV 1 [28]. This was the first study to show that FF clinically has a long duration of action, suggesting that it may be compatible with OD dosing.…”
Section: Phase I and Ii Efficacy Studiesmentioning
confidence: 80%
“…New bronchodilators with a longer duration of action as once daily (OD) therapy have now been developed. Fluticasone furoate (FF) is a novel inhaled corticosteroid (ICS) with a 24-h duration of action while vilanterol trifenatate (VI) is an inhaled selective long-acting β 2 -agonist with fast-onset and prolonged bronchodilatation over 24 h. The combination of FF/ VI has been approved and used in chronic obstructive pulmonary disease as OD maintenance therapy [1][2][3]. This paper reviews the literature supporting the use of the combination of FF/VI as the OD maintenance treatment of asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The same year, the same combination of drugs, doses and delivery system (Relvar Ellipta ® ; GSK, UK) was approved in Japan and the European Union for the treatment of asthma 9. Breo Ellipta (FF [100 or 200 μg]/VI [25 μg]) was approved by the FDA for the maintenance treatment of asthma in April 2015 2.…”
Section: Introductionmentioning
confidence: 99%
“…22 In vivo data showed that both FF 15 and VI 23 are metabolized primarily by the liver enzyme cytochrome P450 (CYP) 3A4; in contrast, neither CYP3A4 24 nor CYP2D6 25 is involved in UMEC clearance. Excretion is almost exclusively by feces for FF, 26 both urine and feces for VI, 20,26 and biliary secretion (and, to a lesser extent, in urine) for UMEC. 21 Two healthy-volunteer dose-finding studies evaluated the PK and pharmacodynamics of the individual components of FF/UMEC/VI administered as a triple combination compared with the dual combinations of FF/VI (Relvar/Breo ELLIPTA; GlaxoSmith-Kline plc, Middlesex, United Kingdom) or UMEC/VI (Anoro ELLIPTA; GlaxoSmithKline plc, Middlesex, United Kingdom) in non-Chinese participants.…”
mentioning
confidence: 99%
“…In vivo data showed that both FF and VI are metabolized primarily by the liver enzyme cytochrome P450 (CYP) 3A4; in contrast, neither CYP3A4 nor CYP2D6 is involved in UMEC clearance. Excretion is almost exclusively by feces for FF, both urine and feces for VI, and biliary secretion (and, to a lesser extent, in urine) for UMEC…”
mentioning
confidence: 99%